Liberté pour Carlos Romero : les étudiants et les autres démocrates emprisonnés (Union Internationale des Étudiants, 1971)
Portrait of Carlos Romero, segmented as if he was behind bars Poster advertising campaign for the release of political prisoners in Colombia PO-1518